Airport capacity and development funding : proceedings of the 10th World Airports Conference held in Hong Kong on 29 November - 1 December 1994. (Thomas Telford on behalf of the Institution of Civil Engineers, 1996)
These conference proceedings provide a review of current practice, developments and trends within the air travel industry. Airports covered include Heathrow, Berlin, Oslo, Zhengzhou and Bangkok.